Examination of pre-service mathematicsteachers' orchestration types during technology-enhanced lessons - AKKOÇ, HATİCE (My University, 2022)
Although the literature uses the metaphor of orchestration for different purposes, it points out the notion of coordination in general. Instrumental orchestration is a theoretical framework of mathematics education research that uses the orchestration metaphor. This theory explores how teachers integrate technology in their classrooms and coordinate tools. Teachers create sets of instruments with available tools and use specific orchestration types. This study analyzes the orchestration types that pre-service mathematics teachers preferred in technology-enhanced microteaching practices. For this aim, we video-recorded micro-teaching lessons of five pre-service teachers who were senior students enrolled in a four-year teacher preparation program at a state university in Istanbul, Turkey. We provided pre-service teachers with a blackboard, a projector, a smartboard, and the desired number of computers and calculators in the classroom. They organized the classroom environment and chose orchestration types as they wanted. Another source of data was their lessons plans and teaching notes. We conducted the content analysis using Atlas.ti software to analyze lesson videos, lesson plans, and teaching notes using content analysis. We specified the orchestration types (e.g., technical demo, board instruction, link screen-board) and the regions where the orchestration types took place to explore which region pre-service teachers concentrated on during their lessons. Data analysis implied four regions: board, screen, board-screen, and technology-free regions. Findings indicated that pre-service mathematics teachers used the "board instruction" orchestration throughout their lessons, despite having sufficient technological opportunities. In addition, although there is an adjustable board that allows positioning the screen side by side, they used the "link screen-board” orchestration type less than expected. It was notable that they did not use the "technical demo", "Sherpa at work" and "spot and show" orchestration types. We found that the blackboard was the most preferred region and that pre-service teachers preferred a traditional teaching approach. We will discuss the implications of findings to address how to develop the knowledge and skills for technology integration in teacher preparation courses and the professional development of teachers.
Keywords: instrumental orchestration; technology-enhanced mathematics teaching; pre-service mathematics teachers; technology integration